Performance evaluation of a 3-level ANPC photovoltaic grid-connected inverter with 650V SiC devices and optimized PWM - Barater, Davide; Concari, Carlo; Buticchi, Giampaolo; Gurpinar, Emre; De, Dipankar; Castellazzi, Alberto (IEEE, 2016)
Photovoltaic (PV) energy conversion has been on the spotlight of scientific research on renewable energy for several years. In recent years the bulk of the research on PV has focused on transformerless grid-connected inverters, more efficient than traditional line transformer-based ones, but more critical from a power quality point of view, especially in terms of ground leakage current. Neutral point clamped (NPC) inverters have recently gained interest due to their intrinsically low ground leakage current and high efficiency, especially for MOSFET-based topologies. This paper presents an active NPC (ANPC) topology equipped with 650 V SiC MOSFETs, with a new modulation strategy that allows to reap the benefits of the wide-bandgap devices. An efficiency improvement is obtained due to the parallel operation of two devices during the freewheeling intervals. Simulations and experimental results confirm the effectiveness of the proposed converter.